Ketidakadilan Gender dalam Keluarga: Studi Kasus Perempuan Desa Samaelo Kabupaten Bone - Umar, Andi Mardiah; Tenri Awaru, Andi Octamaya (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2024)
This research aims to find out: forms of gender injustice in the family in Samaelo Village, factors that cause gender injustice, the impact of gender injustice in the family for women. This type of research is qualitative research with purposive sampling technique with 4 informants from housewives who have jobs. The collection techniques are observation, interview and documentation. The data analysis technique in this research is qualitative analysis with stages (1) data reduction (2) data presentation and (3) conclusion. The results showed that: (1) the forms of gender injustice that still occur and can be found in families in Samaelo Village are subordination, stereotyping, domestic violence and double burden; (2) the factors that cause gender injustice to still occur in families are economic factors and cultural factors, namely the patriarchal system which until now still dominates the culture of society; (3) the impact of gender injustice on women is the rise of child marriage which triggers other problems such as children's education must be stopped, the emergence of economic problems and due to unstable emotions that trigger continuous arguments that lead to domestic violence and even divorce.